Humidified and Heated Cascade Impactor for Aerosol Sizing - Majoral, Caroline; Coates, Allan L.; Le Pape, Alain; Vecellio, Laurent (Frontiers in Bioengineering and Biotechnology, 2020)
Aerosol sizing is generally measured at ambient air but human airways have different temperature (37°C) and relative humidity (100%) which can affect particle size in airways and consequently deposition prediction. This work aimed to develop and evaluate a new method using cascade impactor to measure particle size at human physiological temperature and humidity (HPTH) taking into account ambient air conditions. A heated and humidified trachea was built and a cascade impactor was heated to 37°C and humidified inside. Four medical aerosols [jet nebulizer, mesh nebulizer, Presurized Metered Dose Inhaler (pMDI), and Dry Powder Inhaler (DPI)] under ambient conditions and at HPTH were tested. MMAD was lower at HPTH for the two nebulizers; it was similar at ambient conditions and HPTH for pMDI, and the mass of particles smaller than 5 μm decreased for DPI at HPTH (51.9 vs. 82.8 μg/puff). In conclusion, we developed a new method to measure particle size at HPTH affecting deposition prediction with relevance. In vivo studies are required to evaluate the interest of this new model to improve the precision of deposition prediction.